Surveillance of nosocomial infections in Dr. Cipto Mangunkusumo National General Hospital, Jakarta, 1999-2002 (Faculty of Medicine Universitas Indonesia, 2004)
Nosocomial infection are one of the main problem in hospital which are associated with significant morbidity, mortality and increased economic cost. Surveillance should be attempted regularly to obtain local data of incidence of nosocomial infections, types of infection, pathogen and resistance pattern. We reported the results of nosocomial surveillance in Dr. Cipto Mangunkusumo National General Hospital, Jakarta, in year 1999 to 2002. The data were obtained from surveillance, conducted by Nosocomial Infection Control Committee. Surveillance were performed to patient in risk of nosocomial infections such as underwent surgical procedure, urinary catheter, peripheral or central venous catheter, ventilator and other invasive procedure. Criteria for nosocomial infection which were used, based on technical guidelines of nosocomial infection in Dr. Cipto Mangunkusumo National General Hospital, year 1999; which referred to CDC definition of nosocomial infections. Incidence rate of nosocomial infections in year 1999, 2000, 2001 and 2002 were 1.1, 0.9, 0.6 and 0.4 % respectively. Type of nosocomial infection include catheter related, surgical wound, urinary tract and respiratory tract infections, ranged between 0 to 5.6 %. Gram negative bacteria consist of Pseudomonas sp, Enterobacter aerogenes, Escherichia coli, Proteus mirabilis were the most common nosocomial pathogen. Gram positive bacteria consist of Staphylococcus epidermidis, Staphylococcus aureus and Streptococcus anhemolyticus. Trend of increasing incidence of Gram positive nosocomial infection also showed in our surveillance. Mostly Gram negative bacteria had been resistant to penicillin, co amoxicillin-clavulanic acid and 3rd generation cephalosporin, but still sensitive to 4th generation cephalosporin and aminoglycoside. The Gram positive bacteria were still sensitive to penicillin, co amoxicillin-clavulanic acid, 4th generation cephalosporin and aminoglycoside. (Med J Indones 2004; 13: 107-12) Keywords : nosocomial infection, surveillance, resistance pattern